Work, retirement and working out: the construction of exercise and the social world of retired women. Issue 3 (27th May 2017) - Mobily, Kenneth E.; Smith, Alexa K.; Chmielewski, Kristen
ABSTRACT: The purpose of the study was to determine how retired women interpreted their exercise with respect to defining physical activity versus activity in general, identifying why they began and continued exercise, and knowing how much was 'enough' exercise. The results suggested four main themes. First, social support and socializing were important aspects of exercise that helped women complete any given session and 'stick with it'. Second, women said that they felt better after they exercised and worse if they missed a class. Third, several women reported a 'work-like' sense of accomplishment after completing exercise classes; some described using exercise class as an organizing element in the day, something structured, scheduled and predictable, much in the way work imparts order to the day while employed. Lastly, some of the women indicated that they were busy, especially when asked about staying active, leading us to conclude that staying active may comingle with exercise.